Exploring students’ difficulties and strategies in listening comprehension - Illa Rahmatin; Asnawi Muslem; Dian Fajrina (Universitas Islam Negeri Ar-Raniry, 2026)
This study investigates students’ difficulties in mastering listening comprehension and the strategies they employ to overcome difficulties in the English Education Department of UIN Ar-Raniry, Banda Aceh. This research aims to identify the types of listening difficulties experienced by students across semester levels and to examine the learning strategies they use based on Oxford’s (1990) Strategy Inventory for Language Learning (SILL). This study employed a mixed-method design combining quantitative and qualitative approaches. The participants consisted of 104 students from different semester levels selected through stratified sampling. Quantitative data were collected using a questionnaire adapted from SILL, with mean scores categorized according to Oxford’s rating scale. Qualitative data were gathered through focus group discussions (FGD) and analyzed using Miles and Huberman’s (1992) interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that students experience listening difficulties at a medium level across five main indicators: accent and intonation, sentence structure, keyword identification, distinguishing key information, and understanding real-life situations. Among these, accent variation and sentence complexity were reported as the most challenging aspects. In terms of strategies, cognitive strategies emerged as the most frequently used, followed by compensation and social strategies, while memory, metacognitive, and affective strategies were used at a medium level. Higher-semester students demonstrated advanced strategic awareness and use of metacognitive and social strategies compared to lower-semester students. The findings contribute theoretically to the understanding of listening comprehension difficulties and strategy use in EFL contexts and provide practical implications for lecturers to design more strategy-oriented listening instruction.